2020
DOI: 10.1108/jhr-10-2019-0239
|View full text |Cite
|
Sign up to set email alerts
|

Planning for active office intervention in Thailand: survey and in-depth interview of university employees

Abstract: PurposeThis study aimed to explore knowledge, attitude, behavior and causes of sedentary behavior (SB) among office workers and guidelines for active office intervention.Design/methodology/approachThe study was comprised of a survey and an interview. In total, 39 nonacademic office workers responded to the Past-day Adults Sedentary Time-University (PAST-U) and workplace sitting break (SITBRQ) questionnaire to measure SB level, sitting bout, frequency and duration of sitting interrupted in 1 h and in whole work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, although the passive prompt intervention was only carried out during occupational hours, this study observed no negative compensatory changes in PBs during leisure or over the 24 h period, suggesting that the passive prompt intervention during working hours benefited the participants’ overall day. By implementing passive prompts and reducing the habit of prolonged desk-based sitting when working, positive long-term health impacts may be achieved [ 1 ]. This study observed a reduction in overall 24 h sedentary time (−32.13 ± 9.35 min, p = 0.002) and showed that the time was reallocated between, standing, LIPA, and MVPA, with only the increase in LIPA achieving significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the passive prompt intervention was only carried out during occupational hours, this study observed no negative compensatory changes in PBs during leisure or over the 24 h period, suggesting that the passive prompt intervention during working hours benefited the participants’ overall day. By implementing passive prompts and reducing the habit of prolonged desk-based sitting when working, positive long-term health impacts may be achieved [ 1 ]. This study observed a reduction in overall 24 h sedentary time (−32.13 ± 9.35 min, p = 0.002) and showed that the time was reallocated between, standing, LIPA, and MVPA, with only the increase in LIPA achieving significance.…”
Section: Discussionmentioning
confidence: 99%
“…Developments in technology have led to a significant reduction in the requirement for physical activity (PA) due to the automation and mechanisation of society [ 1 , 2 ], leading to an increase in desk-based occupations. Many individuals with desk-based occupations remain sedentary for prolonged periods of time, owing to the nature of their work [ 3 ].…”
Section: Introductionmentioning
confidence: 99%